A thematic mapping study of mathematical creativity: Bridging creative thinking and attitude toward mathematics - Yudha, Adinda Salshabilla; Rosnawati, Raden (Universitas Hamzanwadi, 2025)
Creativity is a key 21st-century competence, especially vital in mathematics education. This study presents a systematic literature review and thematic mapping analysis of mathematical creativity from 2016 to 2025, using data from the Scopus database analyzed via RStudio Biblioshiny and the PRISMA framework. It explores three core questions: the evolution of research themes in mathematical creativity, the thematic linkage between creative thinking and attitudes toward mathematics, and pedagogical approaches that connect both constructs. Bibliometric analysis reveals mathematical creativity as a central and evolving theme, prominently positioned in co-occurrence networks and thematic quadrants. Creative thinking and attitudes toward mathematics appear within the same thematic cluster, indicating a strong cognitive-affective connection. Emerging research also identifies ethnic factors and environmental literacy as potential mediators in this relationship. These findings suggest that Realistic Mathematics Education (RME), particularly models incorporating ethnic contexts and environmental themes, may serve as effective pedagogical strategies. Such approaches have the potential to enhance both creative thinking and positive attitudes toward mathematics, contributing meaningfully to the broader discourse on mathematical creativity.